New inspiration on effective development of tight reservoir in secondary exploitation by using rock mechanics method. Issue 1 (January 2016) - Du, Shuheng; Shi, Yongmin; Guan, Ping; Zhang, Yuguang
This study attempted to raise new significant inspiration on effective development of tight reservoir in secondary exploitation by using rock mechanics method. After refitting the conventional tri-axial rock mechanics testing instruments, a set of probing experiments on rock mechanics determination were performed. Results show that mechanism of the influence of confining pressure on the Young's modulus is different from that of the pore pressure. The physical significance of the slope and intercept value in Young's modulus changing curves were analyzed; two kinds of mechanisms which cause changes of Young's modulus were raised. Meanwhile, we put forward the concept of "microscopic" anisotropy and introduce the coefficient of "S" and "H" to quantitatively characterize the relative difference on impact extent, where pore pressure and confining pressure could lead to change in Young's modulus and the size of microscopic anisotropy of Young's modulus. We predicted the size of microscopic anisotropy of Young's modulus in Qijiagulong district of Daqing Oilfield by using the above method. The conclusion could provide scientific basis for judging the well pattern adaptability, preponderant direction of water flooding, the reservoir rock fracturing, and optimization design of fracturing parameters.